Evaluación del efecto de la reutilización de la levadura para el proceso de fermentación en la producción de cerveza artesanal del estilo blonde ale en la Cervecería OD Colombia (2020)
The present project was based on the comparative analysis of sugar consumption performance, expressed in terms of apparent attenuation in addition to the variables: alcohol production, cell growth and sensory properties obtained by reusing Safeale yeast US-05 for fermentation of Blonde Ale style craft beer an experimental volume of 4 L for each generation in duplicate. An experimental culture medium was developed from the conditions of preparation of craft beer at plant level. An inoculation rate was performed for the experiments of 2.52 * 107 viable cells which was met for all experimental fermentations. The fermentation time of the experiments was 8 days at a temperature of 17 ° C ± 1 ° C, ambient pressure and an initial must density of 1,050 according to the process carried out at the Cervecería OD Colombia.